The Impact of Storms on Legionella pneumophila in Cooling Tower Water, Implications for Human Health - Brigmon, Robin L.; Turick, Charles E.; Knox, Anna S.; Burckhalter, Courtney E. (Frontiers in Microbiology, 2020)
1 At the US Department of Energy’s Savannah River Site (SRS) in Aiken, South Carolina, cooling tower water is routinely monitored for Legionella pneumophila concentrations using a Direct Fluorescent Antibody (DFA) technique. Historically, 25-30 operating SRS cooling towers have varying concentrations of Legionella in all seasons of the year with patterns that are unpredictable. Legionellosis, or Legionnaire’s Disease (LD), is a pneumonia caused by Legionella bacteria that thrive both in manmade water distribution systems and natural surface waters including lakes, streams, and wet soil. LD is typically contracted by inhaling L. pneumophila, most often in aerosolized mists that contain the bacteria. At the SRS, L. pneumophila is typically found in cooling towers ranging from non-detectable up to 108cells/L in cooling tower water systems. Extreme weather conditions contributed to elevations in L. pneumophila to 107-108cells/L in SRS cooling tower water systems in July-August 2017. L. pneumophila densities in Cooling Tower 785-A/2A stayed in the 108cells/L range despite biocide addition. During this time other SRS cooling towers did not demonstrate this L. pneumophila increase. No significant different was observed in the mean L. pneumophila mean densities for the towers (p<.05). There was a significant variance observed in the 285-2A/A Tower L. pneumophila results (p<.05). Looking to see if we could find “effects” led to model development by analyzing 13 months of water chemistry and microbial data for the main factors influencing the L. pneumophila densities in five cooling towers for this year indicated chlorine (Cl) and dissolved (D) oxygen had a significant impact (p<.0002) on cooling tower 785A/2A. Thus, while the variation in the log count data for the A-area tower is statistical greater than that of the other four towers, the average of the log count data for the A-Area tower was in line with that of the other towers. It was also observed that the location of 785A/2A and basin resulted in more debris entering the system during storm events. Our results suggest that future analyses should evaluate the impact of environmental conditions and Cooling Tower design on L. pneumophila water densities and human health.